The home of God : a brief story of everything - Volf, Miroslav; McAnnally-Linz, Ryan. (Grand Rapids, Michigan : : Brazos Press, a division of Baker Publishing Group, 2022)
"Addressing the aching sense that there is nowhere we truly belong, this book tells the "story of everything" in which God creates this world as the home for humans and for God"--
Includes bibliographical references and index.
Keywords: Home -- Religious aspects -- Christianity; Creation